Research on sealing performance evaluation of CO2 storage in salt-gypsum caprocks of depleted gas reservoirs - JIANG Beibei, LIU Jiabo, ZHANG Guoqiang, WANG Dong, LI Ying, LUO Hongwen, ZHOU Lang (Youqicang pingjia yu kaifa)
In the context of the global carbon neutrality strategy, greenhouse gas emissions —mainly CO₂— are continuously rising, exerting adverse effects on the global climate, ecosystems, and human life. Geological storage of CO2 is an important technological approach to achieving carbon neutrality targets. As sealing barriers within potential storage formations, the sealing property of caprocks is crucial for the long-term or even permanent CO2 storage. Salt-gypsum caprocks exhibit favorable properties such as low porosity, low permeability, high structural stability, and high breakthrough pressure, making them promising candidates for long-term and secure CO2 storage. However, their physicochemical characteristics differ significantly from those of other lithological caprocks, posing challenges to evaluating their sealing performance for CO2 storage. Therefore, there is an urgent need to establish an evaluation method tailored to salt-gypsum caprocks. Firstly, based on the Analytic Hierarchy Process (AHP), a comprehensive evaluation index system was developed by considering key influencing factors, such as macro indicators, micro indicators, and breakthrough pressure, affecting the sealing performance of caprocks. Four grading levels were defined for each index, and the influence weight of each index on the sealing performance of salt-gypsum caprocks was determined. Secondly, by integrating the Fuzzy Comprehensive Evaluation Method, the total weight for evaluating the sealing performance of salt-gypsum caprocks for CO2 storage was calculated. This resulted in the development of a comprehensive evaluation method of CO2 storage sealing tailored to these types of caprocks. Finally, the method was applied to the Gaoshiti-Moxi block in the Sichuan Basin as a case study, where the CO2 storage sealing performance of its potential salt-gypsum caprock in a depleted gas reservoir was systematically evaluated. The results revealed that the total weight of the sealing performance evaluation of Gaoshiti-Moxi structural gas reservoir caprocks ranged from [2.5,3.0), corresponding to a grade of “relatively good”, indicating a relatively strong capacity for CO2 storage. This suggested the site was suitable for the future application of Carbon Capture and Storage (CCS) technology. The research results can provide technical guidance for site selection and storage safety evaluation of CO2 storage in depleted gas reservoirs with salt-gypsum caprocks.